2012
DOI: 10.1016/j.ophtha.2011.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ocular Alignment with Adjustable Sutures in Adults Undergoing Strabismus Surgery

Abstract: Objective To assess whether outcomes of strabismus surgery are improved by using the adjustable suture technique and to determine which subgroups of strabismus patients benefit most from the adjustable suture technique. Design A retrospective chart review. Participants Five hundred thirty-five adults who had strabismus surgery between 1989–2010. Methods Success was defined as ≤10 prism diopters (PD) for horizontal deviations and ≤2 PD for vertical deviations. Differences in the proportion of successful s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 24 publications
4
40
1
Order By: Relevance
“…17 Many studies have found adjustable sutures to be a beneficial technique. [18][19][20] In our study, patients who underwent strabismus surgery with adjustable sutures were more likely to have a successful outcome (adjustable, 63%; no adjustable, 38%), but this difference did not quite reach significance (p = 0.06), likely due to the small sample size.…”
Section: Discussioncontrasting
confidence: 56%
“…17 Many studies have found adjustable sutures to be a beneficial technique. [18][19][20] In our study, patients who underwent strabismus surgery with adjustable sutures were more likely to have a successful outcome (adjustable, 63%; no adjustable, 38%), but this difference did not quite reach significance (p = 0.06), likely due to the small sample size.…”
Section: Discussioncontrasting
confidence: 56%
“…18 However, many other studies have found a benefit to the adjustable suture technique. [19][20][21] Outcomes of the use of adjustable sutures specifically for abducens paresis has not been previously evaluated to our knowledge. We found that patients who underwent adjustable sutures were more likely to have a successful outcome (71% versus 49%), but this difference was not statistically significant, likely due to our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…6 Zhang et al studied two surgeons who frequently used adjustable sutures and one surgeon who did not. 11 Another recent study noted a higher success rate in patients who selected adjustable sutures compared with patients who did not. 12 Demonstrations of adjustable suture efficacy from the retrospective literature have limitations.…”
Section: Introductionmentioning
confidence: 99%